B108. Diagnostic and Therapeutic Approaches in Sleep Apnea 2012
DOI: 10.1164/ajrccm-conference.2012.185.1_meetingabstracts.a3845
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Of CPAP Adherence Promotion By Peer Buddies With Sleep Apnea

Abstract: BRIEF SUMMARYCurrent knowledge/Study Rationale: Poor adherence to the primary treatment of OSA-continuous positive airway pressure (CPAP) therapy-is common, and there is a paucity of easily accessible yet costeffective interventions that could promote CPAP adherence. Promoting adherence to therapy through peer-driven intervention is cost-effective and has met with modest success in other chronic conditions such as HIV, heart failure and diabetes mellitus, but whether such a peer-driven intervention can improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…A meta-analysis of all 6 RCTs demonstrated a clinically significant difference in PAP usage of 1.2 h/night (95% CI: 0.3 to 2.0 h/night) (see supplemental material, Figure S80). Similarly, a meta-analysis of 5 of these RCTs 86,214,[216][217][218] reporting on obtaining PAP usage > 4 h/night found behavioral interventions were associated with a clinically significant odds ratio of 3.1 (95% CI: 1.7 to 5.9) for being adherent (see supplemental material, Figure S81).…”
Section: Adherence (Behavioral Interventions)mentioning
confidence: 95%
See 2 more Smart Citations
“…A meta-analysis of all 6 RCTs demonstrated a clinically significant difference in PAP usage of 1.2 h/night (95% CI: 0.3 to 2.0 h/night) (see supplemental material, Figure S80). Similarly, a meta-analysis of 5 of these RCTs 86,214,[216][217][218] reporting on obtaining PAP usage > 4 h/night found behavioral interventions were associated with a clinically significant odds ratio of 3.1 (95% CI: 1.7 to 5.9) for being adherent (see supplemental material, Figure S81).…”
Section: Adherence (Behavioral Interventions)mentioning
confidence: 95%
“…8 A total of 18 RCTs were identified that evaluated the use of some combination of an educational, behavioral, or troubleshooting intervention as an adjunct to initiation of PAP therapy compared to PAP therapy with standard of care alone on PAP adherence, sleepiness, and QOL. 207,[214][215][216][217][218][219][220][221][222][223][224][225][226][227][228][229][230] Data were not available to assess the effect of these interventions on sleepiness or QOL. Given the substantial heterogeneity in the interventions assessed, the TF decided to divide interventions into one of three broad categories: ( 1 All studies included in this assessment compared at least one of these interventions to a standard of care which varied substantially across studies in terms of the level and intensity of care provided, resulting in heterogeneity across studies.…”
Section: Educational Behavioral and Troubleshooting Interventions With Pap Versus Pap Alonementioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear if the study monitors employed any type of individual encouragement or help other than providing "the best mask fit" to improve CPAP usage even though there are methods that can improve adherence. 8,9,10 It is abundantly clear that more hours with CPAP results in improved measures such as lower blood pressure, reduced sleepiness and increased quality of life. 11,12 One would assume that such improvements would similarly translate to fewer cardiovascular events.…”
Section: Co M M Entarymentioning
confidence: 99%
“…32 There is also evidence that peer coaching could help improve PAP adherence. 33 Our study, also known as the Improving CPAP Adherence Program (I-CAP) study, aimed to provide a multidimensional treatment framework based on shared decision-making, patient activation, and caregiver engagement. We hypothesized that our I-CAP study would promote and support active patient participation, and that it would engage the caregiver to enhance long-term PAP acceptance and adherence.…”
Section: Introductionmentioning
confidence: 99%